2016
DOI: 10.1158/1940-6207.capr-16-0122
|View full text |Cite
|
Sign up to set email alerts
|

Grape Seed Procyanidin Extract Mediates Antineoplastic Effects against Lung Cancer via Modulations of Prostacyclin and 15-HETE Eicosanoid Pathways

Abstract: Grape seed procyanidin extract (GSE) has been reported to exert antineoplastic properties via the inhibition of cyclooxygenase-2 (COX-2)/prostaglandin E 2 (PGE 2 ) eicosanoid pathways. In addition, ample data link carcinogenesis to inflammatory events involving other major eicosanoid metabolic pathways, including prostacyclin (PGI 2 ) and 15-hydroxyeicosatetraenoic acid (15-HETE). We therefore evaluated the effects of GSE on prostacyclin synthase (PTGIS)/PGI 2 and 15-lipoxigenase-2 (15-LOX-2)/15-HETE productio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
25
0
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 27 publications
1
25
0
2
Order By: Relevance
“…The other two pathways that are involved in the formation of midchain HETEs are LOX and COX-2 enzymes. 5-LOX, 12-LOX, and 15-LOX enzymes metabolize AA to produce 5-, 12-, and 15-HETE, respectively (Porro et al, 2014;Radmark et al, 2015;Mao et al, 2016). In addition, it has been reported that minor quantities of midchain HETEs are produced by COX-2 enzyme (Bai and Zhu, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The other two pathways that are involved in the formation of midchain HETEs are LOX and COX-2 enzymes. 5-LOX, 12-LOX, and 15-LOX enzymes metabolize AA to produce 5-, 12-, and 15-HETE, respectively (Porro et al, 2014;Radmark et al, 2015;Mao et al, 2016). In addition, it has been reported that minor quantities of midchain HETEs are produced by COX-2 enzyme (Bai and Zhu, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…GSE is mainly used as a health food supplement to improve cardiovascular health [ 3 ]. Preclinical studies have shown antineoplastic effects of GSE against a variety of cancers, including lung cancer [ 4 9 ]. We recently reported that modulations of oncogenic microRNA (miRNA) or oncomir miR-19a/b, contributed to the antineoplastic properties of GSE against non-small cell lung cancer (NSCLC) and bronchial premalignant cells [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…En este estudio, solo el número de frutas estuvo según lo sugerido. A pesar de, toda la comunicación social que existe a nivel mundial para el consumo de frutas por su alto contenido de polifenoles que contribuyen como agente protector antioxidante, a reducir riesgos de cáncer (Fu et al, 2011;Li et al, 2016) y las verduras igualmente, ante su protección anticancerígena y de enfermedades crónicas (Zhang et al, 2015), al menos se observó en este estudio gran consumo de una de las frutas como es la uva (Vaid & Katiyar, 2015;Mao et al, 2016) y del tomate como vegetal (Trejo et al, 2013;Aizawa et al, 2016) quienes son reconocidos por su gustación, más que el valor nutricional.…”
Section: Discussionunclassified